Inhibition of Chlamydia trachomatis growth in McCoy, HeLa, and human prostate cells by zinc. - Greenberg, S B (1985)
Zinc salts (10(-4) and 10(-5) M) inhibited the number of Chlamydia trachomatis inclusions in McCoy, HeLa, and primary human prostate epithelial cell cultures. Addition of zinc salts 1 h before or 24 h after inoculation with C. trachomatis was found to inhibit growth. Both C. trachomatis serotype D and a lymphogranuloma venereum strain were inhibited by the zinc salts. Although the mechanism of inhibition is not known, the continued presence of the zinc appeared necessary for maximal effect. At the concentrations tested, zinc was not directly toxic to the McCoy cells. These results suggest that the levels of zinc in prostatic secretions may be sufficient to preclude the recovery of chlamydia in the diagnostic laboratory or to inhibit chlamydia from infecting the prostate in vivo.